Methodology for Visual Quality Estimation of Aerial and Satellite Images - I. Anikeeva; A. Chibunichev (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The most widely used remote sensing data are photographic survey systems mounted on aircraft and spacecraft.The problem of remote sensing data quality control arises when evaluating the survey sensor’s functionality as a part of validation tests and during topographic surveys as a part of technical check activities. The problem of shortcomings and, sometimes, complete normative regulation absence of main concepts and unified approaches to the methodology of aerial and satellite images quality estimation is raised in the paper. To develop a methodology for visual quality estimation, a number of basic tasks have been formulated and proposed. The main stages description of a proposed methodology are given. The operation principle flowchart of visual quality estimation is presented. The developed methodology makes it possible to estimate the aerial and satellite images visual quality based on quantitative indicators in automatic mode.